COCOPLOT: COlor COllapsed PLOTting software Using colour to view 3D data as a 2D image. Issue 1 (28th July 2022) - Druett, Malcolm K; Pietrow, Alexander G M; Vissers, Gregal J M; Robustini, Carolina; Calvo, Flavio
ABSTRACT: Most modern solar observatories deliver data products formatted as 3D spatiotemporal data cubes, that contain additional, higher dimensions with spectral and/or polarimetric information. This multidimensional complexity presents a major challenge when browsing for features of interest in several dimensions simultaneously. We developed the COlor COllapsed PLOTting (COCOPLOT) software as a quick-look and context image software, to convey spectral profile or time evolution from all the spatial pixels ( x, y ) in a 3D [ n x, n y, n λ ] or [ n x, n y, n t ] data cube as a single image, using colour. This can avoid the need to scan through many wavelengths, creating difference and composite images when searching for signals satisfying multiple criteria. Filters are generated for the red, green, and blue channels by selecting values of interest to highlight in each channel, and their weightings. These filters are combined with the data cube over the third dimension axis to produce an n x × n y × 3 cube displayed as one true colour image. Some use cases are presented for data from the Swedish 1-m Solar Telescope and Interface Region Imaging Spectrograph, including H α solar flare data, a comparison with k -means clustering for identifying asymmetries in the Ca ii K line and off-limb coronal rain in IRIS C ii slit-jaw images. These illustrate identification by colour alone using COCOPLOT of locations including line wing or central enhancement, broadening, wing absorption, and sites with intermittent flows or time-persistent features. COCOPLOT is publicly available in both idl and python .